Mobiliário como integrador do espaço urbano: Estudos sobre diretrizes de projeto e gestão em Uberlândia (MG) - Fontes, Mateus Finotti (2019)
This research aims to understand some relationships of urban furniture and the urban space of the city of Uberlândia / MG, considering their functions, aesthetics and symbolism through the perception of users of such equipment. To this end, an extensive study has been done on the subject, passing through several spheres that contemplate urban furniture, such as definition of terms and classification of objects, considering several authors and legislations, their interference in the urban landscape, issues such as ergonomics and anthropometry in addition to an assessment on the perception of users of the above furniture. We surveyed the amount of urban furniture in a central region of the city: Sérgio Pacheco Square (urban furniture in leisure environments), Clarimundo Carneiro Square (urban furniture in historical environments) and João Pinheiro Avenue around the area of connection between the two squares (implementation of urban furniture in linear flow environments, streets and sidewalks), after the key equipment were selected to be analyzed with users. Legal issues were raised with the city government regarding the subject of finding out how it is treated and managed by the public administration. Criteria were established to interview some people who make use of the equipment in order to understand their perception about its usage and how appropriate they are. With the compilation of all the data mentioned above, the main objective of this research was achieved: guidelines were established for the creation of projects by designers, architects, engineers, and any other professionals who may work in this area of urban furniture taking into account the real needs of users for the city of Uberlândia / MG. Guidelines were also prepared for the management of these objects by the competent municipal authorities in order to bring better quality, durability and maintenance of equipment as well as beautification and appropriation by users of the city of Uberlândia. The guidelines presented here are not understood as general rules to be applied, but as a starting point so that professionals who are interested. Despite being a study in the environment of the city of Uberlândia / MG, it is understood that this research may also benefit several other cities that have similar characteristics.